2021
DOI: 10.3390/polym13142287
|View full text |Cite
|
Sign up to set email alerts
|

Thermophysical Properties of Larch Bark Composite Panels

Abstract: The effects of using 100% larch bark (Larix decidua Mill) as a raw material for composite boards on the thermophysical properties of this innovative material were investigated in this study. Panels made of larch bark with 4–11 mm and 10–30 mm particle size, with ground bark oriented parallel and perpendicular to the panel’s plane at densities varying from 350 to 700 kg/m3 and bonded with urea-formaldehyde adhesive were analyzed for thermal conductivity, thermal resistivity and specific heat capacity. It was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 83 publications
3
21
0
Order By: Relevance
“…Such materials are, among several other used natural alternatives such as bark, cellulose, hemp, kenaf, flax, feathers, sheep wool, or wood fibers [ 7 , 19 , 20 , 21 ], the natural vegetable fiber-based thermal insulations that are gaining ground in the construction market [ 22 ] because demand for green building materials is rising sharply [ 23 ]. Among natural fibers, one of the most researched materials is the use of straw bales as building materials [ 24 , 25 ] because of their low thermal conductivity and high specific heat capacity, and hence low thermal diffusivity and good thermal insulation capability, especially with fibers randomly oriented and perpendicular to heat flow, and low environmental impact if the straw bale selection used for the straw-based building is suitable [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such materials are, among several other used natural alternatives such as bark, cellulose, hemp, kenaf, flax, feathers, sheep wool, or wood fibers [ 7 , 19 , 20 , 21 ], the natural vegetable fiber-based thermal insulations that are gaining ground in the construction market [ 22 ] because demand for green building materials is rising sharply [ 23 ]. Among natural fibers, one of the most researched materials is the use of straw bales as building materials [ 24 , 25 ] because of their low thermal conductivity and high specific heat capacity, and hence low thermal diffusivity and good thermal insulation capability, especially with fibers randomly oriented and perpendicular to heat flow, and low environmental impact if the straw bale selection used for the straw-based building is suitable [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the first base model [ 45 ], the material density and the bulk density of the insulation were sufficient because the glass fibers are both solids. However, the influence of the density and porosity of the heat transfer in natural-based materials also depends on the type of raw materials as well as the size and orientation of fibers, particles, or grains [ 19 , 51 ]. In the case of straw stems, one more density parameter must be introduced to take into consideration the porosity of the stems and the gaps among the stems.…”
Section: Introductionmentioning
confidence: 99%
“…The EDPS (Extended Dynamic Plane Source) method was used to measure physical properties. It is one of the non-stationary methods for this purpose [32, EDPS method is based on the Dynamic Plane Source (DPS) method, andit can be investigate the thermal conductivity, thermal diffusivity and specific heat capacity conductivity materials (λ ≤ 2 W•m −1 •K −1 ) [34,35]. Figure 5 shows the device scheme The EDPS (Extended Dynamic Plane Source) method was used to measure thermophysical properties.…”
Section: Thermophysical Propertiesmentioning
confidence: 99%
“…It is one of the non-stationary methods for this purpose [32,33]. The EDPS method is based on the Dynamic Plane Source (DPS) method, andit can be used to investigate the thermal conductivity, thermal diffusivity and specific heat capacity of low-conductivity materials (λ ≤ 2 W•m −1 •K −1 ) [34,35]. Figure 5 shows the device scheme.…”
Section: Thermophysical Propertiesmentioning
confidence: 99%
“…The thermal conductivity value of the developed sample was 0.293 W/mK. In addition, some researchers have reported the valorization of tree bark fiber for thermal insulation panels, such as spruce, black locust, larch, and poplar bark [ 16 , 17 , 18 , 19 , 20 , 21 ]. These investigations showed that bark residue is a potential alternative raw material for efficient bio-based thermal insulation.…”
Section: Introductionmentioning
confidence: 99%